Initial colonization of Long Island, New York by the eastern coyote, Canis latrans (Carnivora, Canidae), including first record of breeding - Christopher Nagy; Mark Weckel; Javier Monzón; Neil Duncan; Michael R. Rosenthal (Check List, 2017)
Coyotes (Canis latrans Say, 1823) have increased their range dramatically over the past century. Formerly restricted to western North America, they now roam across the continent, in many habitats including large cities. One of the last areas in North America without coyotes has been Long Island, NY, a 3629 km2 island in the New York metropolitan area. Here we summarize all verified accounts of coyotes on Long Island, including the first record of breeding. There are few coyotes on Long Island currently; however, given the history of coyote success, we expect coyotes to establish a growing population there in the near future.